Enhancing Educational Quality Through Effective Communication in Private Universities - M Mahbubi; Abd. Hamid Cholili; Ali Anhar Syi’bul Huda; Shuhada (Journal of Education and Learning Sciences, 2025)
This study examines the role of communication among stakeholders in enhancing the quality of education at private universities (PTS) in Probolinggo. By analyzing the interactions between university leadership, faculty, students, alumni, and local government, this research explores how effective communication fosters collaboration and institutional development. A qualitative approach is employed through interviews, observations, and literature analysis to identify key factors contributing to educational quality improvement. Findings indicate that effective communication enhances student performance, institutional reputation, and graduate employability. For instance, the implementation of regular academic forums and open dialogues between university leadership and faculty has facilitated curriculum alignment with industry needs, improving the relevance of education. Additionally, alumni engagement through mentoring programs and partnerships with businesses has expanded career opportunities for graduates, demonstrating the impact of communication in building professional networks. The study also clarifies that "educational outcomes" in this context encompass student academic achievement, institutional accreditation, and the effectiveness of educational policies. Based on these findings, the research recommends establishing a more structured communication system, utilizing digital platforms to enhance stakeholder interaction, and strengthening feedback mechanisms to ensure continuous educational quality improvement. These recommendations provide valuable insights for other higher education institutions seeking to optimize communication strategies for academic and institutional advancement. Keywords: Stakeholder Communication, Educational Quality Improvement, Student Performance, Institutional Development, Graduate Employability.